Systematic Review of Antimicrobial Drug Prescribing in Hospitals - Peter Davey (Emerging Infectious Diseases, 2006)
Prudent prescribing of antimicrobial drugs to hospital inpatients may reduce incidences of antimicrobial drug resistance and healthcare-associated infection. We reviewed the literature from January 1980 to November 2003 to identify rigorous evaluations of interventions to improve hospital prescribing of antimicrobial drugs. We identified 66 studies with interpretable data, of which 16 reported 20 microbiologic outcomes: gram-negative resistant bacteria, 10 studies; Clostridium difficile–associated diarrhea, 5 studies; vancomycin-resistant enterococci, 3 studies; and methicillin-resistant Staphylococcus aureus, 2 studies. Four studies provided strong evidence that the intervention changed microbial outcomes with low risk for alternative explanations, 8 studies provided less convincing evidence, and 4 studies provided no evidence. The strongest and most consistent evidence was for C. difficile–associated diahrrea, but we were able to analyze only the immediate impact of interventions because of nonstandardized durations of follow-up. The ability to compare results of studies could be substantially improved by standardizing methods and reporting.